The Permanent Input Hypothesis : The Case of Textbooks and (No) Student Learning in Sierra Leone - Sabarwal, Shwetlena (World Bank Group, Washington, DC, 2014)
A textbook provision program in Sierra Leone demonstrates how volatility in the flow of government-provided learning inputs to schools can induce storage of these inputs by school administrators to smooth future consumption. This process in turn leads to low current utilization of inputs for student learning. A randomized trial of a public program providing textbooks to primary schools had modest positive impacts on teacher behavior but no impacts on student performance. In many treatment schools, student access to textbooks did not actually increase because a large majority of the books were stored rather than distributed to students. At the same time, the propensity to save books was positively correlated with uncertainty on the part of head teachers regarding government transfers of books. The evidence suggests that schools that have high uncertainty with respect to future transfers are more likely to store a high proportion of current transfers. These results show that reducing uncertainty in school input flows could result in higher current input use for student learning. For effective program design, public policy programs must take forward-looking behavior among intermediate actors into account.